Study of cocaine seizures through a spatial approach in a northeastern municipality for 2018 (Research, Society and Development, 2022)
It is known that the disorders arising from the increase in the use of drugs, especially cocaine, are increasing, since it has differentiated use patterns, making it difficult to fight. Epidemiological data on this topic are still scarce and insufficient and, observing this fact, the present study proposes to contribute to research in the area addressing cases of cocaine seizure through spatial analysis in the municipality of Campina Grande, Paraíba, for the year 2018. This is a descriptive, cross-sectional, retrospective and quantitative study, using data from the Forensic Laboratory Nucleus of Campina Grande of the Scientific Police Institute (NULF-CG / IPC), and of the files filed with the Narcotics Court of the District of Campina Grande. Categorical variables were presented using descriptive statistics and for data analysis and treatment, the chi-square test and Fisher's exact test were used considering 5% of the significance level (p